Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Find the roots of this equation: (x+5)(x+9)=0

Sagot :

Answer:

x=-5, x=-9

Step-by-step explanation:

Use zero product property to set each term to 0: x+5=0, x+9=0.

x=-5, x=-9

Answer:

x=-5 and x=-9

Step-by-step explanation:

First you use the first bracket to give you:

x+5=0

so x=-5

Then you use the second bracket to give you:

x+9=0

so x=-9